1998
DOI: 10.1046/j.1432-1327.1998.2570021.x
|View full text |Cite
|
Sign up to set email alerts
|

Alliinase [S‐alk(en)yl‐ L‐cysteine sulfoxide lyase] from Allium tuberosum (Chinese chive)

Abstract: Alliinase [S-alk(en)yl-L-cysteine sulfoxide lyase], a pyridoxal-phosphate-(Pxy-P)-dependent enzyme, is responsible for the degradative conversion of S-alk(en)yl-L-cysteine sulfoxide to volatile odorous sulfurcontaining metabolites in Allium plants. We have purified alliinase from shoots of Allium tuberosum (Chinese chive) to apparent homogeneity by SDS/polyacrylamide gel electrophoresis. A cDNA clone encoding alliinase was isolated from a cDNA library constructed from whole plants of A. tuberosum by hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…garlic cloves (Mazelis and Crews, 1968), onion bulbs (Tobkin and Mazelis, 1979), leek (Allium porrum; Lohmuller et al, 1994), Chinese chive (Allium tuberosum; Manabe et al, 1998), and wild garlic/ramson (Allium ursinum; Landshuter et al, 1994). Previous reports have shown that garlic (Nock and Mazelis, 1986), leek (Won and Mazelis, 1989), onion (Tobkin and Mazelis, 1979), and Welsh onion (Allium fistulosum; Fujita et al, 1990) alliinases are glycoproteins, and all alliinases have been shown to be pyridoxal 5#-P (PLP) dependent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…garlic cloves (Mazelis and Crews, 1968), onion bulbs (Tobkin and Mazelis, 1979), leek (Allium porrum; Lohmuller et al, 1994), Chinese chive (Allium tuberosum; Manabe et al, 1998), and wild garlic/ramson (Allium ursinum; Landshuter et al, 1994). Previous reports have shown that garlic (Nock and Mazelis, 1986), leek (Won and Mazelis, 1989), onion (Tobkin and Mazelis, 1979), and Welsh onion (Allium fistulosum; Fujita et al, 1990) alliinases are glycoproteins, and all alliinases have been shown to be pyridoxal 5#-P (PLP) dependent.…”
mentioning
confidence: 99%
“…Previous reports have shown that garlic (Nock and Mazelis, 1986), leek (Won and Mazelis, 1989), onion (Tobkin and Mazelis, 1979), and Welsh onion (Allium fistulosum; Fujita et al, 1990) alliinases are glycoproteins, and all alliinases have been shown to be pyridoxal 5#-P (PLP) dependent. Isolated alliinases vary in molecular mass depending on the source of the enzyme, ranging from 67 kD in Chinese chive (Manabe et al, 1998) to 580 kD in leek (Won and Mazelis, 1989). The number of enzyme subunits has been shown to differ depending on the source of the alliinase, ranging from one for Chinese chive to 12 for leek.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Radiolabeled BOCL-175 was then used to screen a broccoli cDNA library prepared as described in Ref. 22 using RNA extracted from 6-month-old field-grown influorescences. Approximately 280,000 individual unamplified plaques were screened as described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 280,000 individual unamplified plaques were screened as described in Ref. 22 and one full-length clone (BOCL-3), and several partial clones were isolated and sequenced in both directions, as described previously (11), after subcloning into pBluescript II.…”
Section: Methodsmentioning
confidence: 99%